Chapter 1 - Solid lipid nanoparticles (SLN): prediction of toxicity, metabolism, fate and physicochemical properties - Campos, J. R. (2020)
Various controlled delivery systems have been promoted in the recent decades in order to improve solubility, stability as well as bioavailability of poorly absorbed drugs. Solid lipidic nanoparticles (SLNs) are made of solid lipid matrix and a surfactant layer, and they have as characteristics the fact that can load poorly water-soluble drugs, delivering them at defined rates and thus enhancing their intracellular uptake. These colloidal drug delivery systems defend the drug against chemical degradation and achieve controlled drug release, once the drug is loaded in the solidified lipid state, i.e., the drug is entrapped in biocompatible lipid core and surfactant at the outer surface. They exhibit as advantages the biocompatibility, matrix with lipophilic nature protecting the incorporated active compounds against chemical degradation, drug targeting, controlling the release profile and elevated quantity of lipophilic drug payload. Regarding solidified emulsion technologies, the literature describes various methods for the production of SLNs, such as high shear homogenization and ultrasound, high pressure (hot and cold homogenization), oil/water and water/oil/water microemulsions, as well as solvent evaporation. Although compositions used consist of physiological lipids and surfactants, they are safe and are approved for human use. The toxicological profile of lipid nanoparticles is mainly dependent on the physicochemical properties, i.e., mean particle size and size distribution and zeta potential. Toxicological testing nevertheless documents that lipid nanoparticles are safe drug carriers for several administration routes. This chapter reviews the two main aspects of inÂ vitro tests and secondly the physicochemical properties of lipid nanoparticles that may pose risks for dermal, ocular, and oral toxicity.